Editorial for ‘Issue focus on 2nd Costa Rica Biophysics Symposium - March 11th–12th, 2021’ - Chaves, Gustavo (2022)
This Editorial describes both the motivation for, and the five articles appearing in, the Issue Focus dedicated to the 2nd Costa Rica Biophysics Symposium which was held in March 2021. Some recent history about both the symposium and developments in science occurring within Costa Rica is described.